Clonal lineages, antimicrobial resistance, and pvl carriage of staphylococcus aureus associated to skin and soft-tissue infections from ambulatory patients in Portugal - Ferreira, Carolina (2021)
Staphylococcus aureus (S. aureus) is a leading cause of skin and soft-tissue infections (SSTIs) in the community. In this study, we characterized a collection of 34 S. aureus from SSTIs in ambulatory patients in Portugal and analyzed the presence of Panton–Valentine leucocidin (PVL)-encoding genes and antibiotic-resistance profile, which was correlated with genetic determinants, plasmid carriage, and clonal lineage. Nearly half of the isolates (15, 44.1%) were methicillin-resistant Staphylococcus aureus (MRSA) and/or multidrug resistant (MDR). We also detected resistance to penicillin (33/34, 97.1%), fluoroquinolones (17/34, 50.0%), macrolides and lincosamides (15/34, 44.1%), aminoglycosides (6/34, 17.6%), and fusidic acid (2/34, 5.9%), associated with several combinations of resistance determinants (blaZ, erm(A), erm(C), msr(A), mph(C), aacA-aphD, aadD, aph(3′ )-IIIa, fusC), or mutations in target genes (fusA, grlA/gyrA). The collection presented a high genetic diversity (Simpson’s index of 0.92) with prevalence of clonal lineages CC5, CC22, and CC8, which included the MRSA and also most MDR isolates (CC5 and CC22). PVL-encoding genes were found in seven isolates (20.6%), three methicillin-susceptible Staphylococcus aureus (MSSA) (ST152-agrI and ST30-agrIII), and four MRSA (ST8-agrI). Plasmid profiling revealed seventeen distinct plasmid profiles. This work highlights the high frequency of antimicrobial resistance and PVL carriage in SSTIs-related S. aureus outside of the hospital environment.